Redox Host–Guest Nanosensors Installed with DNA Gatekeepers for Immobilization‐Free and Ratiometric Electrochemical Detection of miRNA. Issue 12 (16th November 2021) - Xie, Xiyue; Wang, Zhenqiang; Zhou, Meizhen; Xing, Yuxin; Chen, Yuhua; Huang, Jixi; Cai, Kaiyong; Zhang, Jixi
Abstract: Electrochemical nanosensors by integrating functional nucleic acids and nanomaterials hold a great promise in the fast detection of biomarkers, yet the current systems possess limitations on the accessibility of target–probe and probe–electrode interactions and the repeatability of detection. Herein, a host–guest assembly strategy is developed to build redox nanosensors for an immobilization‐free and ratiometric electrochemical detection system. Specifically, electroactive molecule ( E m ) guests are loaded in porous hosts of polydopamine nanoparticles (MPDA) to act as dual‐signal redox reporters. Hybrid DNA probes of G‐quadruplex and a single‐stranded anchor DNA are installed as gatekeepers for sealing the mesopores. Thereby, miRNA triggered E m release by strand displacement reactions and the homogeneous transportation of the hosts/guests to the electrode facilitate the generation of reference signal/response signal at different potentials. Concomitantly applied NIR irradiation boosts the electron transfer from MPDA to the electrode and results in a tenfold increase in the reference signal. Finally, the sensing system through the differential pulse voltammetry method achieves a highly repeatable detection (relative standard deviation 3.8%) of miRNA with a lower detection limit (362 × 10 −15 m ). This attractive system paves the way for rational designs of advanced electrochemical biosensors and smart diagnosis. Abstract : A host–guest assembly strategy is developed to build redox nanosensors for an immobilization‐free and ratiometric electrochemical miRNA detection system through the differential pulse voltammetry method. The homogeneous transportation of the host/guest to the electrode driven by the electric field can greatly improve the accessibility/repeatability in the nanosensors with the heterogeneous sensing interface.